Problematika Pembelajaran Ilmu Shorof Kelas VIIC MTs Nahdlotul Muslimat Surakarta Tahun Ajaran 2024/2025 - Hawariya Halwa (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2025)
This study aims to investigate the learning process and methods used in teaching the science of shorof, the problems encountered, and the solutions implemented to overcome these problems at MTs Nahdlotul Muslimat Surakarta. This research employs a qualitative method with a descriptive approach. The type of research is field research. Data collection techniques include observation, interviews, and documentation. The data analysis method consists of data collection, reduction, and presentation, followed by drawing conclusions. The findings of this study indicate that shorof learning employs three methods: the lecture method, memorization, question-and-answer, and dictation (imla). The linguistic problems include phonetic aspects (pronunciation) related to the articulation of letters (makhārij al-ḥurūf), and the second, related to writing (kitābah). Meanwhile, the non-linguistic problems consist of limited learning time, heterogeneous students, and students’ difficulties in memorizing tashrīf. The solutions proposed are: a) collaborating with tajwīd teachers in pronouncing letters according to their articulation points and characteristics, b) training students’ listening skills by exposing them to Arabic conversations, c) thoroughly understanding the rules of Arabic writing, d) strengthening memorization of forms (shighāt) in an auditory manner, e) increasing the number of shorof lessons to enhance effectiveness, f) grouping students based on their scores and understanding, g) memorizing tashrīf using rhythmic tones.